ショウワキチ シュウヘン ニ オケル 2カショ ノ アデリーペンギン ルッカリー ニ オケル ペンギン コタイスウ ノ ヘンドウ - 星合, 孝男; ホシアイ, タカオ; 松田, 達郎; マツダ, タツロウ; 内藤, 靖彦; ナイトウ, ヤスヒコ; Hoshiai, Takao; Matsuda, Tatsuro; Naito, Yasuhiko (1981)
P(論文) 昭和基地付近にあるアデリーペンギン(Pygoscelis adeliae)のルッカリーのうち, オングルカルベン(69°01'S, 39°26'E)および, まめ島(69°01'S, 39°29'E)のルッカリーにおいて, ペンギン個体数の推移を調査した。オングルカルベンルッカリーでは, 1961-62年繁殖期の個体数は110であり, 1966-67年, 1970-71年には, それぞれ, 103,156であった。ところが, 1971-72年以降, 個体数は著しく減少し1975-76年には1970-71年の約1/3となった。しかし, それ以後は, わずかに減少するに止っている。まめ島ルッカリーにおいても, オングルカルベンと同じ傾向の個体数変動が認められた。観測隊員によるペンギン観察の頻度は, 個体数減少の原因となるほど多いとは考えられず, むしろ, 海氷条件が個体数に影響を与えると考えた方がよさそうである。「ふじ」が昭和基地へ接岸できたか否かを, アデリーペンギンにとっての海氷条件の良否の指標と考えると, 個体数の減少は「ふじ」が接岸できなくなってから起こっていることから, この推定が成り立つ可能性は大きいものと思われる。 The fluctuation of the Adelie penguin population was investigated at the Ongulkalven rookery (69°01'S, 39°26'E) and the Mame-zima rookery (69°01'S, 39°29'E) near Syowa Station (69°00'S, 39°35'E), Antarctica. Number of bird in the Ongulkalven rookery was 110,103 and 156 in the breeding seasons of 1961-62,1966-67 and 1970-71,respectively. From 1971-72 season, the population of penguin began to decrease and in 1975-76 season it reached about one-third of that of 1970-71 season. Thereafter, the reduction of population became gradual. The same tendency in population fluctuation as mentioned above was also observed at the Mame-zima rookery. The disturbance by the expedition members seemed to be little because of the low frequency of their penguin watching. A possible relation between the penguin populations in two rookeries and the sea ice condition in the breeding season was observed. Since Japanese Antarctic Relief Ship, Icebreaker FUJI, succeeded to approach Syowa Station from 1965-66 to 1970-71 seasons but failed after 1971-72 except 1977-78 summer, the ice condition between 1965-66 and 1970-71 breeding seasons seemed to be advantageous to the Adelie penguin but to become unfavorable after 1971-72 season. departmental bulletin paper